Reliability and construct validity of practice of medical doctors on smoking cessation guidelines - Shalihin, Mohd Shaiful Ehsan; Md Aris, Mohd Aznan; Nik Mohamed, Mohamad Haniki; Mohd Rus, Razman; Jamani, Nurjasmine Aida (2016)
Number of active smokers in Malaysia is increasing despite availability of smoking clinics.